A Pengaruh Pendidikan Kewirausahaan Dan Ekspektasi Pendapatan Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Ekonomi Angkatan 2020 Fkip Universitas Jambi - Febrian Fajri, Muhamad; Muazza, Muazza; Syuhada, Siti (Edu Sosial, 2023)
The research conducted aims to determine the effect of entrepreneurship education and income expectations on the interest in entrepreneurship in economics education students class of 2020 FKIP Jambi University. This research is a descriptive quantitative research using the Ex Post Facto research approach. The data collection tool used a questionnaire with the help of the Google form which was distributed to a sample of 71 students. Sampling technique with full sample. The results of this study indicate that: (1) There is an influence of Entrepreneurship Education on Interest in Entrepreneurship in Students. (2) There is an influence between Income Expectations on Interest in Entrepreneurship in Students. (3) There is an influence between Entrepreneurship Education and Income Expectations on Interest in Entrepreneurship in Students. From these results it can be concluded that there is a positive and significant influence between Entrepreneurship Education and Income Expectations on Interest in Entrepreneurship in Students.